Habitat Influences Arthropod Biodiversity - Choo, Hannah; Priest, Aleece; Ruberson, John R. (My University, 2018)
Biodiversity is an important indicator of environmental health. Insects are very interconnected ecologically, very adaptable, and highly diverse, making them excellent indicators for environmental health. Human interference tends to disrupt ecosystems to make them less diverse (Benton et al. 2003). A greater variety of plants should be expected to support a greater variety of insects, aiding environmental health (e.g., Diniz et al. 2010). We tested the effect of degree of habitat disturbance/plant diversity on insect diversity in 6 habitats over three dates, expecting to see greater insect diversity where there is greater plant diversity. We calculated insect biodiversity using Simpson’s Index of Diversity, and found greater insect abundance and diversity in more diverse habitats. Insect diversity is important for habitat health, so as insect diversity declines, other animals in those ecosystems suffer as well, as the food web is disrupted (Kemp and Ellis 2017).
Keywords: Fall 2018